2020
DOI: 10.24198/jkp.v8i1.1190
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Reflections on Challenges and Barriers of Communication in the Intensive Care Unit: A Phenomenology Study

Abstract: Communication among nurses, patients, and families takes an important role in the intensive care unit in which the patients are in critical condition and unable to involve in two-way communication. Research related to effective nurse-patient communication has been done extensively, but the information regarding communication in intensive care unit is still limited. This research aimed to explore nurses’ experiences in the intensive care units in effective communication to patients/patient’s families. This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This makes different perspectives a natural thing to happen, so a communication forum between teams is needed during a pandemic. Communication skills are important and must be continuously improved by every nurse, so that they become a habit in carrying out their duties in providing health services in hospitals (Emaliyawati, Widiasih, Sutini, Ermiati, & Rahayu, 2020). The results of this study indicate that participants need good communication between teams while caring for COVID-19 patients in order to achieve quality nursing care.…”
Section: Discussionmentioning
confidence: 86%
“…This makes different perspectives a natural thing to happen, so a communication forum between teams is needed during a pandemic. Communication skills are important and must be continuously improved by every nurse, so that they become a habit in carrying out their duties in providing health services in hospitals (Emaliyawati, Widiasih, Sutini, Ermiati, & Rahayu, 2020). The results of this study indicate that participants need good communication between teams while caring for COVID-19 patients in order to achieve quality nursing care.…”
Section: Discussionmentioning
confidence: 86%
“…Nurses who interact with patients from different cultures and languages must face constant difficulties and continue to provide services to patients. Studies conducted (Emaliyawati et al, 2020) in West Java show that cultural and linguistic differences can hinder patient and nurse communication. The participants also expressed feelings of chaos and instability related to their situation.…”
Section: Discussionmentioning
confidence: 99%
“…Miscommunication can lead to family misunderstanding of the patient's condition. Emaliyawati et al (2020) reported communication barriers in the ICU between patient families and healthcare workers related to high workload, educational background of the family, cultural differences, and agerelated cognitive decline. Therefore, nurses need to possess therapeutic communication skills and adapt their approach to the family's circumstances.…”
Section: Family Participation During Roundsmentioning
confidence: 99%